Milking time during periods of heat stress: part of the solution or part of the problem? - L. Rocha; Lindsey E. Hulbert; Filippe Scortegagna; Benjamin Voelz; L. Mendonca (Kansas Agricultural Experiment Station Research Reports, 2014)
Milking time may be a stressful event for lactating dairy cows during summer. Increases in body temperatures because of crowding in the milk parlor holding pen may contribute to increased heat stress. The objective of this extension project was to evaluate the effectiveness of heat stress abatement in milking facilities from two Kansas commercial dairies. Vaginal temperatures at milking were lower than vaginal temperatures before milking in one of the dairies. The lower vaginal temperatures at milking, however, were not observed in the other dairy at all milkings, likely because of differences in efficacy of heat abatement strategies. Milking facilities may be one of the factors to aggravate or alleviate heat stress in lactating dairy cows during summer. Key words:; Dairy Day, 2014, Kansas State University, Manhattan, KS, 2014; Dairy Research, 2014 is known as Dairy Day, 2014
Keywords: Dairy Day; 2014; Kansas Agricultural Experiment Station contribution; no. 15-156-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 1111; Dairy cattle; Heat stress; Milking parlor; Cooling